Pengaruh Pengendalian Internal Terhadap Pencegahan Fraud di Rumah Sakit (Studi Empiris pada Rumah Sakit Swasta di Jabodetabek) - Dwi Zarlis (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
This study examined and proved the influence of internal control against fraud in the hospital either simultaneously or partially. This study used a questionnaire survey with 86 respondents taken from 10 hospitals in Jabodetabek. Statistical tests using simultaneous significance test ( F test ) shows the influence of the independent variables with the same independent variable. While significant partial test (t test) showed that the control environment, risk assessment, control activities, information and communication, and monitoring have t results > t table at a significance level of 5%, so partially significant effect have a value < 0.05.